2004
DOI: 10.1007/978-3-540-30117-2_73
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pipelining on Energy per Operation in Field-Programmable Gate Arrays

Abstract: Abstract. This paper investigates experimentally the quantitative impact of pipelining on energy per operation for two representative FPGA devices: a 0.13µm CMOS high density/high speed FPGA (Altera Stratix EP1S40), and a 0.18µm CMOS low-cost FPGA (Xilinx XC2S200). The results are obtained by both measurements and execution of vendor-supplied tools for power estimation. It is found that pipelining can reduce the amount of energy per operation by between 40% and 90%. Further reduction in energy consumption can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 23 publications
0
42
0
2
Order By: Relevance
“…Since both pipelining [Wilton et al 2004] and word-length optimization [Constantinides 2006] can improve performance and reduce power consumption, it would be worthwhile to investigate how these two techniques can be used in automating domain-specific strategies for producing tree-based designs that best meet user requirements in speed, area, and power consumption. More sophisticated comparisons with the latest GPUs from nVidia and AMD/ATI, Altera FPGAs, and the Cell Broadband Engine [Agarwal et al 2008] are also planned.…”
Section: Resultsmentioning
confidence: 99%
“…Since both pipelining [Wilton et al 2004] and word-length optimization [Constantinides 2006] can improve performance and reduce power consumption, it would be worthwhile to investigate how these two techniques can be used in automating domain-specific strategies for producing tree-based designs that best meet user requirements in speed, area, and power consumption. More sophisticated comparisons with the latest GPUs from nVidia and AMD/ATI, Altera FPGAs, and the Cell Broadband Engine [Agarwal et al 2008] are also planned.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that, at a given clock speed, pipelining can reduce the amount of energy per operation by between 40% and 90% for applications such as integer multiplication, CORDIC, triple DES, and FIR filters [65].…”
Section: Low-power System-level Designmentioning
confidence: 99%
“…The datapath power consumption is reduced by 13% using clock gating. Glitch is a spurious transition at a node within a single cycle before the node settles to the correct logic value [10]. Unlike ASICs, in which signals can be routed using any available silicon, FPGAs implement interconnects using fixed metal tracks and programmable switches.…”
Section: Datapath Power Reductionmentioning
confidence: 99%